Integration of critical success factors from demand and supply sides to enhance micro financing framework for micro and small enterprises (mses) in Malaysia - Muridan, Mazliana (2019)
Micro and small enterprises (MSEs) play important roles in the Malaysian economy. Access to financing is one of the main constraints for most micro and small enterprises (MSEs) in business survival. The Malaysian government is aware of the financing issues among micro and small enterprises. Therefore, the National SME Development Council has approved the sustainable microfinance framework in 2006 to improve access for financing from financial institutions. However, there are few weaknesses of the micro financing framework, since many micro enterprises are unable to reach the financing facilities. The existing framework only focuses on the side of financial supply but less attention to the demand side, which is important as guidance for MSEs in obtaining financing. Therefore, this research explored the access to financing for MSEs in Malaysia by enhancing the sustainable microfinance framework for MSEs. A mixed method approach (quantitative and qualitative) employed in this research by implementing survey and case study research design. Surveys were conducted to 321 respondents from MSEs while interviews were conducted to six microfinance providers and ten MSEs. The findings of this research were used to enhance the existing microfinance framework. The new framework was enhanced from the existing microfinance framework by integrating the demand and supply side in the framework. The supply side represents the microfinance providers while the demand side represents MSEs. Several elements had been placed in the demand side such as the sources of financing, the major challenges in getting financing and the success factors of micro financing. On the supply side, few elements were included in strategic initiatives. All those elements provide a better understanding of the strategies in getting financing and yet become a guideline for MSEs to be successful in getting external funds for their businesses.